Valuation of Farfetch Ltd. - Lehocký, Dominik; Schönfeld, Jaroslav; Smrčka, Luboš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
This thesis aims to provide a valuation of Farfetch Ltd in order to validate the massive stock price increase followed by the news on its partnership with Alibaba and Richemont group. Strategic analysis of the company and its environment preceding the valuation has hinted at the company’s favorable position in markets outside of China, where the position looks promising as well; however, it is unlikely the company will ever dominate the Chinese market in a way it has dominated the rest of the world. Following the analysis, key value drivers were estimated, and a valuation using the FCFF DCF model and EV/Revenue ratio followed. The valuation results suggest that the closing price of USD 62.82 per share on December 31, 2020, was highly inflated relative to the estimates of USD 32.21 and USD 35.04 obtained using the DCF model and EV/Revenue model with multiple regression.
Vedoucí práce: Jaroslav Schönfeld
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses